Stability, phonon calculations, electronic structure, and optical properties of a VO2(M) nanostructure: A comprehensive density functional theory study - Mohebbi, Elaheh; Pavoni, Eleonora; Mencarelli, Davide; Stipa, Pierluigi; Laudadio, Emiliano; Pierantoni, Luca (Frontiers in Materials, 2023)
This work aimed to precisely evaluate the physical properties of vanadium dioxide (M), particularly the optical characteristics. We employed different exchange-correlation functionals to determine the phase stability, band gap properties, and optical characteristics of an experimentally recognized monoclinic VO2(M) polymorph. The calculations not only correctly interpreted the VO2(M) origin but also predicted other optical properties including the extinction coefficient (k) and refractive index (n), which have not been reported in experimental measurements. Phonon dispersion calculations confirmed the presence of negative frequencies for acoustic modes in the phononic curves. When the HSE functional correctly reproduced the experimental band gap, here for the first time, our calculations based on PBE and PBEsol yielded non-zero electronic bandgaps of 0.23 and 0.15 eV for bulk VO2(M). Our predictions showed that semi-local functionals can adequately predict the semiconductor properties of VO2(M) and performed better than all previously reported theoretical works on nulled band gaps. In addition to the better prediction of the peak position in the absorption spectra with HSE hybrid functional, this method also reasonably well described the static dielectric constant of 7.54, showing an excellent match to the experimental values. In general, the results of this study reveal that hybrid functionals yield superior outcomes compared to semi-local functionals for optical properties of a VO2(M) polymorph. Our results suggest that the PBEsol + HSE approach allows the efficient characterization of smart materials for electronic and optoelectronic applications.